2013
DOI: 10.1016/j.atmosres.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of atmospheric turbidity over Ghardaïa city

Abstract: International audienceThe atmospheric turbidity expresses the attenuation of the solar radiation that reaches the Earth's surface under cloudless sky and describes the optical thickness of the atmosphere. We investigate the atmospheric turbidity over Gharda¨ıa city using two turbidity parameters, the Linke turbidity factor and the Angstr ¨om turbidity coefficient. Their values and temporal variation are obtained from data recorded between 2004 and 2008 at Gharda¨ıa. The results show that both parameters have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
5
10
0
4
Order By: Relevance
“…We note a maximum of clear days in 2007 for the two methods. This confirms previous results of the Linke turbidity factor obtained from the same data set [8]. We found that it had a lower value during this year.…”
Section: Comparison Of the Results Obtained From The 2 Methodssupporting
confidence: 82%
See 4 more Smart Citations
“…We note a maximum of clear days in 2007 for the two methods. This confirms previous results of the Linke turbidity factor obtained from the same data set [8]. We found that it had a lower value during this year.…”
Section: Comparison Of the Results Obtained From The 2 Methodssupporting
confidence: 82%
“…We note that this parameter has maximum values during the summer months and minimum ones in winter. This result confirms what was found and stated in our previous paper [8]. It is explained by a hot summer climate and winds of the south sectors (Sirocco) that characterize the region of Ghardaïa.…”
Section: Estimation Of the Turbidity Parameterssupporting
confidence: 82%
See 3 more Smart Citations